Mothers' evaluation of cartoons' influence on early childhood children - (:unkn) unknown (ELSEVIER SCIENCE BV, 2010)
The purpose of this study is to investigate mothers' thoughts about the influence of cartoons on their young children. Two hundred twenty three mothers of preschoolers and kindergarteners completed and returned a demographic information form and Mothers' Evaluation of Cartoons questionnaire. ANOVAs were computed to examine the effects of demographic characteristics and television related variables on mothers' thoughts about cartoons. Mothers' educational level, children's age, parent-child length of daily television watching and their perception of television affected their thoughts about cartoons' influence on children. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Cartoons; early childhood children; mothers' thoughts